Design, Development, and Implementation of a Desktop-Based Laundry Management Application for Optimizing Operational Efficiency - Rahmadani, Noni Fauzia; Syahputri, Rifdah; Nugroho, Agung; Nasution, Luftia Rahma; Siregar, Dzilhulaifa; Dewi, Aulia Kartika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Manual management of laundry operations often faces various challenges, such as recording errors, limited monitoring of employee activities, and lack of transparency in financial reporting. To address these issues, this research aims to design and develop a desktop-based laundry management application that integrates order management, problem reporting, and financial management efficiently. The application is designed for three main user roles: staff, shop heads, and owners. Staff are responsible for inputting customer orders and reporting operational issues, shop heads monitor staff activities and handle problems, while owners can access financial reports and order activity recaps to support strategic decision-making. This research employs the Research and Development (R&D) method with the Waterfall software development model, encompassing requirements analysis, system design, implementation, and testing. Data collection was conducted through literature studies and direct observation of operational processes in multiple laundry businesses. The application was developed using the Java programming language and MySQL database and operates locally without requiring an internet connection. Testing results indicate that the system improves order processing efficiency by reducing recording time by approximately X% compared to manual methods, accelerates financial transaction recording, and enhances transparency in operational reporting. With this system, laundry management is expected to become more effective, accurate, and easily accessible to all users.